(untitled) (Global Journal of Management and Business Research, 2023)
The prime objective of this study is to analysis determinates of e-banking service adoption among Economics leadership in banke conomics leadership Evidence from selected Economics leadership economics in bank 20 economics leadership used to achieve the objectives of the study and answer the research questions the study was used mixed research approach which encompasses both qualitative and quantitative research methods In this study the data was collected by using questionnaire data collection method and the data source of the study was primary data source only This descriptive study was conducted based on the data gathered from 20 economics leadership in Economics leadership economics in banks The data collected was analyzed using exploratory statistics and regression analysis A research framework developed based on the Technology Organization Environment Demographic and socio cultural perceived usefulness and Political factors was used to guide the study The study revealed the following major driving determinants of E-banking service adoption Economics leadership economics in bank Perceived Ease of Use PEOU and Perceived Usefulness PU of the technology